The sociology of intellectual life the career of the mind in and around the academy - Fuller, Steve 1959- (Sage, 2009)
"The Sociology of Intellectual Life outlines a social theory of knowledge for the 21st century. Steve Fuller deals directly with a world in which it is no longer taken for granted that universities and academics are the best places and people to embody the life of the mind. While Fuller defends academic privilege, he takes very seriously the historic divergences between academics and intellectuals, attending especially to the different features of knowledge production that they value."--BOOK JACKET.